Pharmacotherapy in benign prostatic enlargement: the impact of tamsulosin and dutasteride on erectile dysfunction - Sajjad, Muddasir; Ashraf, Hamza; Shahzad, Talat; Khan, Nadir Saifullah; Imran, Maryum; Ahmad, Naveed (International Journal of Pathology, 2025)
Background: Benign prostatic enlargement (BPE) becomes increasingly common as men grow older. A wide range of lower urinary tract symptoms (LUTS)occur as the condition progresses. Erectile dysfunction (ED) frequently coexists with these symptoms and may be influenced by the medications used to treat BPE. This study compared the impact of tamsulosin alone with that of the tamsulosin–dutasteride combination on erectile function. Methods: This multicenter cross-sectional study was conducted in the urology and surgical outpatient clinics of two hospitals. A total of 79 sexually active men over the age of 50 with LUTS related to BPE were included. Participants were divided into two groups: Group A (n=41), receiving tamsulosin 0.4 mg daily, and Group B (n=38), receiving a fixed-dose combination of tamsulosin and dutasteride. Erectile function was evaluated using the Sexual Health Inventory for Men (SHIM), a validated questionnaire. Results: In the present study, erectile-function outcomes were closely examined in men treated either with tamsulosin alone or with a tamsulosin–dutasteride combination. When SHIM scores were compared between the two groups, the averages were nearly the same (14.8 ± 6.6 for men receiving tamsulosin only, and 15.7 ± 5.2 for those on the combined regimen; p = 0.48). A similar pattern appeared when erectile-dysfunction severity was analyzed across standard categories (p = 0.62). Erectile dysfunction was widespread in both groups, and the distribution of age and major comorbidities were well balanced at baseline. Conclusion: These results indicate that LUTS/BPH, is likely the primary contributor to sexual difficulties, rather than the specific medication prescribed. These findings can help guide patient counseling, reassuring them that the choice between these common regimens, based on prostate size and symptom severity, may not confer an additional risk to erectile function specifically.